PEDAGOGICAL ASPECTS OF FORMING STUDENTS' AESTHETIC COMPETENCE IN THE PROCESS OF VOCATIONAL TRAINING - Butenko , Volodymyr; Butenko , Natalia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The problem, which in today's conditions has acquired particular relevance, namely the formation of students' competence in certain fields of knowledge, is considered. The essence of the concept of aesthetic competence, the content of the specified process, as well as the nature and methods of their development by students in the process of distance education are revealed. Attention is focused on the fact that aesthetic competence is a multifunctional quality of a person and involves a wide range of professional training. The essential features of aesthetic competence of a person are identified. It was concluded that the optimal approach to solving the problem of forming aesthetic competence should be the consistent and systematic involvement of future specialists in the active development of aesthetic values ​​during professional training.